Security Risks and Threats - Handling, Phenomenology, Mapping - - GJurovski, Marjan; Nikolovski, Marjan; Gerasimoski, Saše (My University, 2020)
The script at hand is a result of a pilot research project, presenting some of the preliminary findings on security risks that the Macedonian society and state are facing today. It represents a first step in creating a model for thorough monitoring and mapping of security risks and threats by the Faculty of Security in Skopje which the authors intend to establish. The text adds to the publications and studies by the Faculty of Security, such as the Security Index 1 and 2 published by the Konrad Adenauer Foundation and the Opinion of Citizens on Security and Security Threats in the Republic of North Macedonia. With the aim to increase the number of published texts on security risks and threats, this time, we decided to carry out a preliminary research on security risks in the Republic of North Macedonia: mapping, etiology, phenomenology and handling security risks. Four years ago, the Faculty of Security carried out a scientific research on the opinion of citizens on security and security threats. The present script complements that study and revisits some of the security risks and threats. Particularly, the text published by the Konrad Adenauer Foundation aims at establishing a scientific approach to clarifying the process of mapping the elements of a risk, i.e., gaining information on identified dangers, on the exposition to potential risk elements, on their vulnerability, as well as on the capacity (resources) of the system to manage crises. This information could be used to prevent and manage potential risks and to cope with evoked consequences. The first assessment of risks and threats to national security in the Republic of North Macedonia was the Defence Strategy of the Republic of North Macedonia published in 1998. The terms used in that document were "danger" and "source of threat", while the National Conception on Security and Defence as of 2003 referred to the terms "risks and threats to national security". Threats had been assessed for the needs of the defence sector even before those two strategic documents were published, but those assessments were not available to the public. Thenceforth, the Republic of North Macedonia had publicly assessed risks and threats. The Law on Crisis Management as of 2004 defined "risks and dangers" to national security and the term "threats to the security of the Republic". A detailed assessment of risks and threats to national security was published in the Strategic Defence Review (SDR) in 2004. The first part of the text at hand contains a detailed analysis and explanation of the risks and threats to national security that resulted from the pilot research. Some of them are defined within the above-mentioned strategic documents of the Republic of North Macedonia. 10 SECURITY RISKS AND THREATS - HANDLING, PHENOMENOLOGY, MAPPING - Assuming that we are living in a very risky society with a growing number of increasingly fluid and diverse security risks, we base our study on a contemporary theoretical framework in which today's risks are considered as a societal and security problem. Above all, we were determined to assess whether we encounter the basic features of security risks typical of globalised and postmodern societies in the context of the conditions of today's society and the setup of the state and its security agencies. Today, security risks represent the predominant topic in our discussions on security. However, we are lacking scientific and research results which would determine the threats from today's types of security risks concerning, above all, the vital interests and the safety of our citizens. While the number of scientific studies on security risks in the Republic of North Macedonia is very low, the existing ones also lack solid theoretical elaboration regarding their subject. In the present study, we refer to the results from the research on the expert community "The Study of Security Risks in the Republic of North Macedonia", which was based on a theoretical study of the different approaches to defining security risks. The study deals with the expert community, i.e. representatives of institutions with direct responsibilities in dealing with security risks and threats. The fast development of science, technology, new global processes and types of international cooperation has set new standards and values. The fast pace of changes has led to international security – and, as a consequence, national security – being exposed to new types of serious threats. Discussing the dangers and risks of the new millennium, we can state that, today, we are facing fewer risks which were typical of the last century, such as war, aggression, etc. The threats to national security, values and interest are becoming more complex and multiple and less predictable, coming from different directions, which makes them harder to analyse and control. The state community has always been exposed to threats, however, their form and intensity have changed. The severity of the threats of the 21st century lies in the use of the information infrastructure for attacking values. These threats make it impossible to guarantee citizens' life and health, seriously affecting their values and interests. The threats of the new millennium can only be addressed and responded to by means of an internationally devised security policy which the national security policies are based upon.1 The aim of the Republic of North Macedonia's security policy is to provide protection and security to its citizens regarding many kinds of external as well as internal influences and threats, including the area of security, economy, politics, environment, culture, etc. The main threats to security are the tensions and antagonisms that result from inter-ethnic conflicts, extreme nationalism, faulty reforms and economic 1 National security policy is understood as a complex and interdependent system of measures, plans and programmes which the Republic of North Macedonia will undertake for the protection, maintenance and improvement of the state's and its citizens' security in accordance with political, economic, defence, interior, security, social, ecological and other resources. 11 Marjan Gjurovski Marjan Nikolovski Saše Gerasimoski inefficiency, huge and frequent environmental and/or technological disasters which have a great impact on society. Besides the weak economy and the political, social and ethnic situation, we would like to point out the new types of threats, such as international terrorism, organised crime (human, drugs and arms trafficking, money laundering, illegal migration), militant nationalism, fundamentalism, etc. These threats can directly or indirectly affect the state and its security, as well as undermine a society's security and its democratic and economic foundations by weakening the state authorities and thus making people loose their trust in the rule of law. Notwithstanding the authorities' attempts to detect and manage potential threats to the state's security in time, today, we are facing a serious political, economic and security crisis, which is likely to pose a risk to the very existence of the state. Unfortunately, this situation has been lasting for too long, starting from the request of the then opposition for the government to resign, to form a transitional government and to call parliamentary snap elections. The inoperability of the institutions turned out to be a fertile ground for organised crime and corruption, while foreign investments and the economy decreased. Additionally, the migration crisis had a direct impact on the economic, political and security system of the Republic of North Macedonia. Against this background, and having in mind the pressing issue of research on security risks, the Faculty of Security, being a science and research institution of higher education, trains professionals whose basic task is to detect, prevent and avert risks in time, in order for them not to become larger-scale threats. Based on its professional potential, long-lasting practical experience and scientific and research potential, the main task of the Faculty of Security is to reflect on and analyse societal phenomena, including security risks that can threaten national as well as regional security.
Keywords: SECURITY RISKS, HANDLING, PHENOMENOLOGY, MAPPING